2018
DOI: 10.1055/s-0043-124078
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of EUS-guided fine needle biopsy in pancreatic mass lesions

Abstract: Background and study aim  Due to the scarcity of specific data on endoscopic ultrasound (EUS)-guided fine-needle biopsies (SharkCore) FNB in the evaluation of pancreatic lesions, we performed a prospective study of the diagnostic performance of EUS SharkCore FNB in patients with pancreatic lesions. The aim of this study was to evaluate the diagnostic accuracy. Patients and methods  Single-center prospective study of 41 consecutive patients referred for EUS-FNB from October 2015 to April 2016 at our center. EUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Recently there has been a paradigm shift in tertiary centers from EUS-FNA/Tru-Cut to EUS-FNB for tissue procurement; this was due to the improved diagnostic accuracy and the availability ofROSE [ 12 ]. Recent data on several new FNB needles have shown impressive tissue acquisition and a high rate of solid tissue cores available for more detailed analysis by pathology [ 15 - 17 ]. Earlier studies have shown that these needles are at least as good as standard FNA needles, while they offer additional tissue for special stains with fewer needle passes overall [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been a paradigm shift in tertiary centers from EUS-FNA/Tru-Cut to EUS-FNB for tissue procurement; this was due to the improved diagnostic accuracy and the availability ofROSE [ 12 ]. Recent data on several new FNB needles have shown impressive tissue acquisition and a high rate of solid tissue cores available for more detailed analysis by pathology [ 15 - 17 ]. Earlier studies have shown that these needles are at least as good as standard FNA needles, while they offer additional tissue for special stains with fewer needle passes overall [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…EUS‐FNA has been the main modality for pancreatic solid mass lesion sampling for several years with a sensitivity of 85% to 87% and a specificity of 96% to 98% . In recent years, there has been a change in the paradigm of tissue acquisition for these lesions with the emergence of next generation core biopsy needles including ProCore (Cook Medical, Bloomington, Indiana), SharkCore (Medtronic, Dublin, Ireland), and more recently, Acquire Franseen (Boston Scientific, Marlborough, Massachusetts) …”
Section: Introductionmentioning
confidence: 99%
“…1,2 In recent years, there has been a change in the paradigm of tissue acquisition for these lesions with the emergence of next generation core biopsy needles including ProCore (Cook Medical, Bloomington, Indiana), SharkCore (Medtronic, Dublin, Ireland), and more recently, Acquire Franseen (Boston Scientific, Marlborough, Massachusetts). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Many studies to date have focused on the ProCore needle. [3][4][5]20,21 Two meta-analyses reported similarly that there was no significant difference in the diagnostic accuracy or the rate of histological core specimen acquisition between the ProCore needle and the standard FNA needles.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the improved histological yield, both the Franseen-tip and the Fork-tip needle demonstrated excellent diagnostic accuracy (> 90 %), with or without presence of rapid onsite evaluation (ROSE) 46 . In addition, they were shown to alleviate the need for ROSE, for both solid pancreatic and non-pancreatic lesions, as well as to reduce the required number of needle passes, with a single pass resulting in an onsite diagnostic accuracy in more than 95 % of patients 46 47 50 51 52 53 54 55 56 .…”
Section: Literature Searchmentioning
confidence: 99%